Comparison of cell disruption method for E. coli BL21-AI expressing recombinant bromelain - Mohd Arshad, Zatul Iffah; Amid, Azura; Othman, Mohd Ezza Faiez (2015)
The often-encountered problem such as protein degradation has driven various methods of cell lysis post fermentation used. In this paper we compare the use of homogenization, sonication, sonication with lysozyme and chemical lysis using B-PER reagent with lysozyme to extract the recombinant bromelain from E. coli BL21-AI. The sonication process is found to be the most effective in releasing recombinant bromelain without needed any pre-treatment. To succeed the cell disruption, the choice of sonication buffer also was investigated including phosphate buffer saline (PBS), PBS containing cysteine and EDTA (PBS-CE), sodium phosphate buffer containing cysteine and EDTA (EB-CE) and sodium phosphate buffer containing sodium chloride (LB). The highest specific enzyme activity was obtained when it was extracted with EB-CE buffer. Under sodium dodecyl sulphate polyacrylamide gel electrophoresis, the recombinant bromelain showed protein band at 55kDa.